Paleoceanographic evolution of the Japan Sea over the last 460 kyr - a coccolithophore perspective - Mariem Saavedra-Pellitero; Karl-Heinz Baumann; Stephen John Gallagher; Takuya Sagawa; Ryuji Tada (PANGAEA, 2018)
A series of surface sediment samples recovered from the Japan Sea (JS) and the East China Sea were analysed using electron microscopy to assess the recent distribution of coccolithophore taxa. Additionally, changes in the intensity of the influx of the Tsushima Warm Current (TWC) were reconstructed in the south-central part of the JS over the last 460 kyr at IODP Site U1427.
Supplement to: Saavedra-Pellitero, M et al. (2019): Paleoceanographic evolution of the Japan Sea over the last 460 kyr – A coccolithophore perspective. Marine Micropaleontology, https://doi.org/10.1016/j.marmicro.2019.01.001